Structural basis for recognition of the malaria vaccine candidate Pfs48/45 by a transmission blocking antibody - Lennartz, Frank (Nat Commun, 2018)
The quest to develop an effective malaria vaccine remains a major priority in the fight against global infectious disease. An approach with great potential is a transmission-blocking vaccine which induces antibodies that prevent establishment of a productive infection in mosquitos that feed on infected humans, thereby stopping the transmission cycle. One of the most promising targets for such a vaccine is the gamete surface protein, Pfs48/45. Here we establish a system for production of full-length Pfs48/45 and use this to raise a panel of monoclonal antibodies. We map the binding regions of these antibodies on Pfs48/45 and correlate the location of their epitopes with their transmission-blocking activity. Finally, we present the structure of the C-terminal domain of Pfs48/45 bound to the most potent transmission-blocking antibody, and provide key molecular information for future structure-guided immunogen design.